Socioeconomic inequalities in child and adolescent mental health in Australia: the role of parenting style and parents' relationships - Nirmal Gautam; Mohammad Mafizur Rahman; Rubayyat Hashmi; Apiradee Lim; Rasheda Khanam (BMC, 2024)
Abstract Background Socioeconomic inequalities in health and their determinants have been studied extensively over the past few decades. However, the role of parenting style and parents' couple relationships in explaining mental health inequalities is limited. Therefore, this study aims to investigate the distributional impact of parenting style (angry parenting, consistent parenting, and inductive parenting) and parents' couple relationships (e.g., argumentative, happy relationships) on socioeconomic inequalities and by extension on mental health status of Australian children and adolescents. Methods This study utilized data from the Longitudinal Study of Australian Children (Waves 1-7), specifically focusing on intact biological parent families, while excluding single-parent and blended-family households. We applied the decomposition index and the Blinder Oaxaca method to investigate the extent of the contribution and temporal impact of parenting style and parents' couple relationships on the mental health status of Australian children and adolescents. Results This study revealed that poor parenting style is the single most important factor that leads to developing mental health difficulties in children and adolescents, especially from low socioeconomic status, and it contributes almost 52% to socioeconomic inequalities in mental health status. Conversely, household income, maternal education, employment status, and parents' couple relationships contributed 28.04%, 10.67%, 9.28%, and 3.34%, respectively, to mental health inequalities in children and adolescents. Conclusion Overall, this study underscores the importance of parenting style and parents' couple relationships as significant predictors of mental health outcomes in children and adolescents. These results highlight the need for targeted interventions to support families from low socioeconomic backgrounds to address the significant mental health inequalities observed in the study population.